To use augmented reality or not in formative assessment: a comparative study. Issue 5 (18th August 2019) - Bhagat, Kaushal Kumar; Liou, Wei-Kai; Michael Spector, J.; Chang, Chun-Yen
ABSTRACT: Augmented reality (AR) is growing in popularity in teaching and learning due in part to powerful new technologies. What has yet to be well established is when and with which learners and learning tasks AR is an effective approach. Therefore, the aim of this study was to examine the effectiveness of using AR-based formative assessment for improving elementary students' learning achievement and motivation in a unit of instruction involving butterflies. A total of 70 students of Grade 4 were selected from an elementary school in Taiwan. The experimental group (35) underwent an AR-based intervention that involved formative assessment using iPads whereas the control group (35) followed the traditional teaching method and formative assessment. One-way Analysis of Co-variance (ANCOVA) and multivariate analysis of variance (MANOVA) were employed to analyze the data obtained. The results indicated that using the AR-based formative assessment improved not only students' learning performance but also learning motivation effectively compared with a traditional formative assessment approach. Therefore, it is recommended to conduct further studies and to consider integrating AR in formative assessments and feedback to improve learning.